1998
DOI: 10.1021/jo972359k
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Cyclization/Silylation of Dienes Containing 1,1-Disubstituted Olefins Using Organolanthanide and Group 3 Organometallic Complexes

Abstract: The catalytic cyclization/silylation reaction of hindered dienes has been investigated using the relatively unhindered complexes Me 2 Si(C 5 H 3 SiMe 3 ) 2 YCH(TMS) 2 and [Cp TMS 2 LnMe] 2 (Ln ) Y, Lu). A wide variety of dienes and trienes bearing a number of functional groups were cyclized, affording silanes containing quaternary centers in a diastereoselective fashion and in good yield. The products can be oxidized using one of several different protocols, yielding alcohols for further functionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 58 publications
4
28
0
Order By: Relevance
“…On the contrary, the 1 H NMR spectra in C 6 D 6 of the complexes, [Me 2 Si(3‐Me 3 SiC 5 H 3 ) 2 ]LnCl (Ln = Nd ( 4 ), Sm ( 5 ), Y ( 6 )), show two resonances for the methyl groups of the SiMe 2 bridge, which is consistent with the formation of meso type compounds. The molecular structure of the dimeric complex, 6 , confirms the isolation of a meso complex 5. It was important to investigate the alkylation of these bridged compounds and their behavior in polymerization of olefins (see also Copolymerization of Ethylene and Butadiene).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…On the contrary, the 1 H NMR spectra in C 6 D 6 of the complexes, [Me 2 Si(3‐Me 3 SiC 5 H 3 ) 2 ]LnCl (Ln = Nd ( 4 ), Sm ( 5 ), Y ( 6 )), show two resonances for the methyl groups of the SiMe 2 bridge, which is consistent with the formation of meso type compounds. The molecular structure of the dimeric complex, 6 , confirms the isolation of a meso complex 5. It was important to investigate the alkylation of these bridged compounds and their behavior in polymerization of olefins (see also Copolymerization of Ethylene and Butadiene).…”
Section: Resultsmentioning
confidence: 92%
“…(C 5 Me 5 ) 2 NdCl 2 Li(OEt 2 ) 2 ( 3 )6 and [Me 2 Si(3‐Me 3 SiC 5 H 3 ) 2 ]YCl ( 6 )5 were prepared according to the literature. The syntheses of ( t BuC 5 H 4 ) 2 NdCl ( 1 ), (Me 3 SiC 5 H 4 ) 2 NdCl ( 2 ), and [Me 2 Si(3‐Me 3 SiC 5 H 3 ) 2 ]NdCl ( 4 ) have been reported previously 4…”
Section: Experimental Partmentioning
confidence: 99%
“…In recent years, organolanthanide and group 3 metallocene complexes have been the focus of numerous investigations into catalytic processes for the cyclization and functionalization of unsaturated organic molecules their reactivity has been harnessed for the hydrogenation, hydrosilylation, and hydroamination of substrates containing one or more double and triple bonds. In suitably arranged substrates, single 3f,4a,b,d,f,h,k or multiple 4j,l,5e cyclization events precede the reaction of the intermediate organometallic with the trapping reagent.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, organolanthanide-catalyzed procedures have been reported to facilitate a cyclization/ silylation reaction of hindered trienes, preparing several [4.3.3]propellanes with reasonable yields, as well as allowing for the synthesis of 245 in 69% yield (Scheme 36). 133 3.7.4 Metathesis: Christmann and co-workers. In a recent study, Christmann and co-workers reported a modular synthesis of functionalized propellanes, including the [3.3.3] propellanedione 252 (Scheme 37).…”
Section: Radical Cyclizationsmentioning
confidence: 99%